Thematic features of periodicals of Kazakhstan in the years of independence - Ashirbekova Г. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2021)
In the article, the author gives an overview of scientific works, collections and encyclopedias related to the history of the press, published during the years of independence. Emphasizing the importance of studying the history of the press, the author highlights the thematic, problematic features of the newspapers “Ak Bosaga” and “Turkistan”. The author focuses on informative, problematic articles and interviews devoted to a number of topical issues published on the pages of the newspaper. The article considers the content of both newspapers in the selection of topics. The article reveals the essence of the raised problem and shows the results of the search for a solution to the topic raised by the journalist. These examples highlight the effectiveness of the press in society. In the first years of independence, the published press withstood market demands and settled on methods of forming a stable readership. The author also considers the contest “Kolan Shash” in the newspaper “Ak Bosaga” as the most rational. The author analyzes articles published in the appendix “Atazhurt” in the newspaper “Turkistan”, dedicated to the problem of Kandastar. The author focuses on the importance of management in the field of modern media giving examples of the management activities of the editors of both publications. The article presents a few examples from his experience for contemporary publications.